2018
DOI: 10.1016/j.sdentj.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oral health education intervention among female primary school children in Riyadh, Saudi Arabia

Abstract: The results of this study showed that an easy-to-organize and inexpensive school-based intervention can, on a short-term basis, be effective in improving the knowledge and self-reported oral health behavior of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 33 publications
7
23
3
4
Order By: Relevance
“…There was no attrition in both groups after intervention. On the other hand, some oral health intervention studies reported that there was drop-out of the participants when assessing the effect of OHE on oral health knowledge and behavior in Wuhan City of China [13], Tehran of Iran [14], and Riyadh of Saudi Arabia [15] which are contrast to the ndings of the present study. The result of China documented that the drop-out rate is small amount and there is no problem in assessing the outcomes [13].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There was no attrition in both groups after intervention. On the other hand, some oral health intervention studies reported that there was drop-out of the participants when assessing the effect of OHE on oral health knowledge and behavior in Wuhan City of China [13], Tehran of Iran [14], and Riyadh of Saudi Arabia [15] which are contrast to the ndings of the present study. The result of China documented that the drop-out rate is small amount and there is no problem in assessing the outcomes [13].…”
Section: Discussioncontrasting
confidence: 99%
“…The present study is compatible with a study conducted among six to eight year old with a sample of 1661 female primary school children in Saudi Arabia to assess the effectiveness of oral health education intervention on oral health knowledge and behavior in which there was signi cant improvement in all knowledge and behavior questions at after intervention (p<0.001) [15]. A study conducted in China to assess the effect of school based OHE intervention on children, mothers and school teachers reported that children in experimental group are more than those in control group regarding adoption of regular oral health behavior such as tooth brushing at least twice a day, dental visits annually, use of uoride toothpaste and less frequent consumption of cakes/biscuits which supports the present study [13].…”
Section: Discussionsupporting
confidence: 62%
“…A study conducted in China to assess the effect of school-based OHE intervention on children, mothers, and school teachers reported that children in the experimental group are more than those in the control group regarding the adoption of regular oral health behavior such as tooth brushing at least twice a day, dental visits annually, use of uoride toothpaste and less frequent consumption of cakes/biscuits which supports the present study [12]. The present study is similar to one study in Bangladesh which showed that overall signi cant improvement was observed in almost all the indicators of knowledge and behavior after OHE compared to before (p<0.001) [15]. When the present study assessed the percentage changes in response to knowledge and behavior on oral health before and after intervention between the two groups, a positive net effect of the intervention was observed.…”
Section: Discussionsupporting
confidence: 89%
“…Different educational interventions about oral health and treatment have been used varying from the simple delivery of information to more complex programs involving psychological and behavior change strategies (Halawany et al, 2018). Knowledge, attitudes, intentions, beliefs, behaviors, use of dental services and oral health status and adoption of lifestyles have all been targeted for change as a result of these interventions, which has stood the test of time as dentistry's most pioneering testimony towards concern with the prevention of oral diseases and creating awareness among the patients about their treatment.…”
Section: Resultsmentioning
confidence: 99%